2019
DOI: 10.4081/jbr.2019.8296
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus mojavensis: biofilm formation and biochemical investigation of its bioactive metabolites

Abstract: Bacillus mojavensis is an endophytic bacterium which has been reported to have fungicidal effect against some phytopathogens. Bioactive secondary metabolites produced by B. mojavensis could have promising applications in agricultural, food industry and clinical fields. The current research has been conducted to: i) evaluate the antagonistic effect of B. mojavensis isolate against some phytopathogens; ii) characterize chemically the principal bioactive substances produced by the studied isolate of B. mojavensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…Bacterial biofilm formation is a serious and ongoing concern in the food industry, mostly due to the ability of biofilm inhabitants to withstand adverse conditions [1,2]. The biofilm formation process is divided into separate stages and includes an attachment step of single cells to a surface, followed by microcolony formation and subsequent growth into mature biofilms with self-production of extracellular polymeric substances (EPS) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial biofilm formation is a serious and ongoing concern in the food industry, mostly due to the ability of biofilm inhabitants to withstand adverse conditions [1,2]. The biofilm formation process is divided into separate stages and includes an attachment step of single cells to a surface, followed by microcolony formation and subsequent growth into mature biofilms with self-production of extracellular polymeric substances (EPS) [3].…”
Section: Introductionmentioning
confidence: 99%
“…The N. AHLs-deficient mutant (ICMP11096 glad -I) and the complemented one (ICMP11096 glad -IR) were evaluated for their ability to inhibit the growth of B. megaterium and E. coli in dual agar plate assay following the method of Lavermicocca et al (1997) as reported by Camele et al (2019). In particular, small masses of fresh bacterial cultures were transferred in the center of 90 mm Ø MMA Petri dishes.…”
Section: Methodsmentioning
confidence: 99%
“…Microbial secondary metabolites (MSM) are the most promising source of novel natural products; hence their discovery and characterization are the objective of many researches for controlling important phyto- and human pathogens [ 53 , 54 , 55 ].…”
Section: Microbial Secondary Metabolitesmentioning
confidence: 99%